KELAS SOSIAL DALAM NOVEL NORTH AND SOUTH, KARYA ELIZABETH GASKELL - PALAR, ELIZABETH RUBY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT North and South is a social novel written by Elizabeth Gaskell. She describes the life situation and condition in the Era of Victoria. Through the unique story of her, Elizabeth Gaskell successfully represents the real event in the reign of Queen Victoria. This research entitled â€œKelas Sosial dalam Novel North and South, Karya Elizabeth Gaskell.â€ It presents the classification of social class and also the effects of social controversy that are reflected through the novel. The purpose of this study is to identify, describe and analyze the social class classification which is reflected in the novel North and South. It also aims to identify and analyze the effects of that social class classification through the character, lifestyle, and pride. The theories that used in this research are by Wellek and Warren (1949) and Karl Marx (1977). The method which is used in this research is descriptive method by Nazir (1988). In analyzing the data, the writer uses intrinsic and extrinsic approaches. The intrinsic approach is used in analyzing characters, social lifestyle, and pride through the people, based on the social classes where they belong. The extrinsic approach is used in analyzing the effects of social classes contradiction to the people in the novel. The result of this research shows the correlation of social class in the Era of Victoria and its effects of social class on society in the novel North and South. Â Keywords: Social Class, Era Victoria, Novel, North and South, Elizabeth Gaskell